2017
DOI: 10.7754/clin.lab.2016.160903
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Abnormal Protein as a Novel Biomarker in Papillary Thyroid Carcinoma

Abstract: TAP may be a novel biomarker for PTC and be useful in the adjuvant diagnosis of PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…19,20 Apart from lung cancer, the existence of TAP expression is evident in the stomach, colorectal, thyroid, and bladder tumors. [9][10][11][12]21 Our research findings add to the general overview of TAP's role in a tumor's development and progression.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…19,20 Apart from lung cancer, the existence of TAP expression is evident in the stomach, colorectal, thyroid, and bladder tumors. [9][10][11][12]21 Our research findings add to the general overview of TAP's role in a tumor's development and progression.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have collected evidence on the critical role that TAP plays in the development and progression of cancer, as well as the regulation of cell proliferation, apoptosis, differentiation, and development. [7][8][9] In gastric cancer patients, the upregulation of TAP was significant compared to healthy volunteers. Also, progression-free survival (PFS) is evident among patients with high TAP levels.…”
Section: Discussionmentioning
confidence: 98%
“…Approximately 70% of proteins in vivo have glycosylation modifications [8]. It has been reported that TAP plays an important role in improving the diagnosis of cancerous tumors, such as bladder, gastric, thyroid, colorectal, and endometrial cancers [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…As the number of cancer cells reaches 100,000 and above [24][25][26], abnormal glycoprotein can be detected in peripheral blood, and its presence indirectly reflects the degree of malignancy of the carcinoma. Since its discovery by Soviet scholars, TAP has been widely used in cancer screening, early diagnosis and evaluation of therapeutic effects on certain tumors [13]. Sun et al found that in patients with malignant tumors of the digestive tract, negative TAP expression in the peripheral blood indicated the complete elimination of tumors.…”
Section: Diagnostic Efficacy Of Tap For Rccmentioning
confidence: 99%
“…Current studies have indicated the involvement of various molecular events in the deterioration of PTC (5,6), including BRAF and RAS mutations, rearrangements of RET protooncogene and the excessive activation of the mitogen-activated protein kinase signal transduction pathway (7)(8)(9)(10). To date, multiple microRNAs (miRs) and long non-coding RNAs (lncRNAs) have been identified as potential molecular biomarkers, including miR-146b-5p and lncRNA HOTTIP, which have been confirmed to participate in the invasion and metastasis of PTC (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%